Implementation of Tawazun Agency Cost in Managing Financial Risk to Improve the Financial Performance of Islamic Boarding Schools: A Case Study of Islamic Boarding Schools in Central Java - Pratiwi, Yunita Niqrisah Dwi; Budi, Budi Cahyono; Dasmadi, Dasmadi (Edumedia Solution, 2025)
This study examines the influence of implementing Tawazun Agency Cost on the management of Financial Risk and its impact on the Financial Performance of Islamic boarding schools in Indonesia. Tawazun Agency Cost is a concept that emphasizes balancing agency costs with prudence and fairness in decision-making between managers and the owners of Islamic boarding schools. Using a quantitative approach, this research employed questionnaires distributed to 100 respondents from Islamic boarding schools registered with the Ministry of Religious Affairs during the 2019–2024 period. Data analysis was conducted using multiple regression and classical assumption tests to ensure the validity of the results. The findings indicate that the application of Tawazun Agency Cost significantly contributes to reducing Financial Risk, which indirectly improves the Financial Performance of Islamic boarding schools. In addition, financial risk was also found to have a negative effect on financial performance, highlighting the importance of effective risk management. This study provides important implications for the management of Islamic boarding schools in optimizing agency costs and risk management to achieve optimal financial performance. The results of this research are expected to serve as a reference for academics and practitioners in developing more effective financial management strategies based on the principles of balance and fairness.